-3(4-2x)=18

Simple and best practice solution for -3(4-2x)=18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(4-2x)=18 equation:


Simplifying
-3(4 + -2x) = 18
(4 * -3 + -2x * -3) = 18
(-12 + 6x) = 18

Solving
-12 + 6x = 18

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + 6x = 18 + 12

Combine like terms: -12 + 12 = 0
0 + 6x = 18 + 12
6x = 18 + 12

Combine like terms: 18 + 12 = 30
6x = 30

Divide each side by '6'.
x = 5

Simplifying
x = 5

See similar equations:

| 0y=ox | | 2(x+2)/8=5 | | 111-3x=15x+23 | | 15x-275=6x-5 | | s=2hw+2wh+2hl | | 6x-119=2x-7 | | 24f-16fg= | | y/2+5=16 | | 6w+w+8w= | | 14x-190=4x-10 | | 6w-w+6w= | | 2x+65=7x-10 | | 9-7X=9X+21 | | -126-8x=16x+18 | | 5(3x+5)-4(2x-3)=5x+3(2x+12)+1 | | 11x+8=8x-29 | | 59-4x=32x+15 | | -28X-6X=12-10X | | 14-9x=199-44x | | 3+7x=27+1x | | 11X+22=4X+113 | | 2.16x^2-5.40x-3.24=0 | | 60-x=19 | | x-6/10+x-4/15=x+2/6 | | 12*(x-2)+6*(5-x)=4x-6 | | x^4+12x^3+36x^2-64=0 | | 5w^8-45w^7-50w^6=0 | | 3x-4(1-3x)=2x-(x-1) | | 3(x+2)/5=6 | | 4-2(3-2x)=5 | | X+x+x=16 | | 3-5(2x+1)=2x |

Equations solver categories